Highly trans‐Selective Arylation of Achmatowicz Rearrangement Products by Reductive γ‐Deoxygenation and Heck–Matsuda Reaction: Asymmetric Total Synthesis of (−)‐Musellarins A–C and Their Analogues. Issue 31 (24th June 2015) - Li, Zhilong; Ip, Fanny C. F.; Ip, Nancy Y.; Tong, Rongbiao
Abstract Fully functionalized pyranuloses derived from Achmatowicz rearrangement (AR) are versatile building blocks in organic synthesis. However, access to trans‐2, 6‐dihydropyrans from pyranuloses remains underexplored. Herein, we report a new two‐step trans arylation of AR products to access 2, 6‐trans‐dihydropyranones. This new trans‐arylation method built on numerous plausible, but unsuccessful, direct arylation reactions, including Ferrier‐type and Tsuji–Trost‐type reactions, was finally enabled by an unprecedented, highly regioselective γ‐deoxygenation of AR products by using Zn/HOAc and a diastereoselective Heck–Matsuda coupling. The synthetic utility of the reaction was demonstrated in the first asymmetric total synthesis of (−)‐musellarins A–C and 12 analogues in 11–12 steps. The brevity and efficiency of our synthetic route permitted preparation of enantiomerically pure musellarins and analogues (>20 mg) for preliminary cytotoxicity evaluation, which led us to identify two analogues with three‐to‐six times greater potency than the musellarins as promising new leads.